Penilaian Dampak Investasi Sosial Pelaksanaan CSR PT Catur Elang Perkasa Menggunakan Metode Social Return On Investment (SROI) - Annisa Ayu Marsha; Rindang Matoati (Universitas Sultan Ageng Tirtayasa, 2021)
Social Return On Investment analysis is a process of measuring social return values produced by an organization based on cost-benefit analysis, social accounting and social audit. PT Catur Elang Perkasa is a company who actively implementing CSR programs. This study aims to analyze the impact of social investment from the implementation of CSR program by calculating the value of the SROI ratio and the value of financial achievements. The type of data used are primary data and secondary data. The analytical method used is the SROI analysis method consists of six stages analysis. The results showed an SROI ratio of 1.56: 1 means that for every Rp1 invested, produced a social return value of Rp1.56. The value of financial achievements of this research is Rp294 037 274 out of the total input value of Rp188 485 432. The results showed that PT Catur Elang Perkasa has succeeded in creating a social impact that provides benefits to its stakeholders because it has produced a positive SROI ratio.